If it's not what You are looking for type in the equation solver your own equation and let us solve it.
43=x-15
We move all terms to the left:
43-(x-15)=0
We get rid of parentheses
-x+15+43=0
We add all the numbers together, and all the variables
-1x+58=0
We move all terms containing x to the left, all other terms to the right
-x=-58
x=-58/-1
x=+58
| –4p+–2=14 | | 8-1y=10 | | –9n=10−10n | | 2x+2=94 | | (3x+-10)+(x+20)=180 | | 8m-4+5m+3=180 | | 8x-4=-10x+50. | | 74+2x-2=7x+2 | | (x-9)=6 | | -u+1=-2u-9 | | 5x÷5=32 | | a.4a+16=0 | | 17–9x=-26 | | 10x=4x-42 | | 3k-1=7k+4 | | 5-4z=-5z | | 2(x-3)^2+6=38 | | |u|-22=12 | | 3(x + 7) = 36 | | 8(x)=4x+2 | | -17–9x=-26 | | X=-20+5x-11 | | 2x+1=94 | | 8(-6x-6)=-16 | | -9p-8=10-7p | | 17=13+y | | 5x-(3+1)=7 | | 2.25(4x-4=-2+10+12 | | 3x(x^2+7x+10)=0 | | 2(3-6d)=-(5d+1) | | -8w=-9w-9 | | 2÷8+h=-3 |